2008
DOI: 10.1007/s00415-008-0934-3
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob disease: Which diffusion-weighted imaging abnormality is associated with periodic EEG complexes?

Abstract: Serial EEGs are not useful for patients with isolated striatal DWI hyperintensity but will increase diagnostic certainty from "possible" to probable" CJD for patients with cortical DWI hyperintensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 9 publications
(10 reference statements)
2
14
1
3
Order By: Relevance
“…Our patients with probable CJD showed a wide range of age at onset (range 54–80 years, mean 73.5 years). The results are fairly consistent with those of previous studies that focused on asymmetry in clinical, EEG, and MRI abnormalities [2,8,9], but the mean age at symptom onset of our patients was somewhat higher than that of the patients in the previous studies. The asymmetry has been detected at an early stage in 40% of the patients with the MM1 and MV1 subtypes [7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our patients with probable CJD showed a wide range of age at onset (range 54–80 years, mean 73.5 years). The results are fairly consistent with those of previous studies that focused on asymmetry in clinical, EEG, and MRI abnormalities [2,8,9], but the mean age at symptom onset of our patients was somewhat higher than that of the patients in the previous studies. The asymmetry has been detected at an early stage in 40% of the patients with the MM1 and MV1 subtypes [7].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a high consistent correlation was noted among clinical presentation and PSWC and brain MRI-DWI findings in our patients. Kandiah et al [8] suggested that EEG-PSWC findings were well correlated with cortical lesions on brain MRI-DWI scans, but not with striatum lesions in probable and possible CJD patients. In addition, they also found that 11 out of 14 patients showed an asymmetric distribution of the lesions on DWI.…”
Section: Discussionmentioning
confidence: 99%
“…Restricted diffusion and DW-MRI signal hyperintensity have been found in the basal ganglia, thalamus, and cortex of CJD patients (60). Again, the proposed explanations for restricted diffusion vary with the CJD subtype but may be related to intraneuronal microvacuolation (57), prion protein deposition, and spongiform change (61). The combination of DW-MRI with FLAIR imaging has sensitivity and specificity reported at Ͼ91 to 98% (59,62).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of DW-MRI with FLAIR imaging has sensitivity and specificity reported at Ͼ91 to 98% (59,62). Those sequences are important for early detection to inform appropriate diagnostic testing (61) and to enable timely intervention as new therapies are developed (59). Although only a small number of studies have used MRI to investigate animal models of prion disease, it has been shown that focal blood-brain barrier disruption occurs in a hamster scrapie model (63), that there are increases in T2 measurements in the septum, hippocampus, thalamus, and cortex of mice inoculated with 139A scrapie (64), and that the diffusion of tissue water was significantly reduced in the late preclinical period in mice inoculated with ME7 scrapie (65).…”
Section: Discussionmentioning
confidence: 99%
“…[16] Difüzyon MRG'de kortikal sinyal artışı olan hastaların hepsinde EEG'de periyodik deşarjlar gözlenmektedir. [20] Beyin omurilik sıvısında 14-3-3 proteininin saptanması CJH tanısını destekler. [2] Çeşitli çalışmaların sonucunda 14-3-3 proteininin hastalık için ortalama duyarlılık ve özgüllüğü %92 olarak hesaplanmıştır.…”
unclassified